Massive Acetaminophen Overdose Treated Successfully with N-Acetylcysteine, Fomepizole, and Hemodialysis - Michael H. Chiu; Natalia Jaworska; Nicholas L. Li; Mark Yarema (Case Reports in Critical Care)
Acetaminophen overdose is one of the most common causes of acute hepatic failure in the developed world. There is strong evidence for N-acetylcysteine (NAC) as a safe and effective antidote for acetaminophen toxicity. However, there is less clarity in the management of massive overdoses (acute, single ingestions>500 mg/kg with 4-hour equivalent concentrations ~6000 μmol/L) which are often associated with metabolic acidosis and multiorgan dysfunction. In such ingestions, the role of adjuvant treatments such as fomepizole and extracorporeal removal is unclear. We present a case of a 20-year-old female presenting with an acute ingestion of over 120 grams (1764.7 mg/kg) and an acetaminophen concentration of 5880 μmol/L who developed refractory shock, decreased level of consciousness, and metabolic acidosis requiring mechanical ventilation and vasopressor support. She was treated with gastric decontamination with activated charcoal, IV NAC, fomepizole, and hemodialysis. The patient had complete clearance of acetaminophen by 32 hours after presentation and normalization of her acid base and hemodynamic status without any organ failure. This case highlights the potential benefit of a triple strategy of NAC, fomepizole, and early hemodialysis in massive acetaminophen overdose, potentially sparing complications of prolonged intubation and ICU hospitalization.